2020
DOI: 10.1111/nmo.13827
|View full text |Cite
|
Sign up to set email alerts
|

Fair reliability of eckardt scores in achalasia and non‐achalasia patients: Psychometric properties of the eckardt spanish version in a multicentric study

Abstract: Background: Eckardt symptom score (ESS) is the most used tool for the evaluation of esophageal symptoms. Recent data suggest that it might have suboptimal reliability and validity. The aims of this study were as follows: (a) Develop and validate an international Spanish ESS version. (b) Perform psychometric ESS evaluation in patients with achalasia and non-achalasia patients. Methods: Eckardt symptom score translation was performed by Delphi process. ESS psychometric evaluation was done in two different sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…To evaluate convergent validity, several self‐report symptomatic scores were filled by patients, for the evaluation of mood [EHAS and Hospital Anxiety and Depression Scale (HADS) and esophageal symptoms (Eckardt score, Gastroesophageal Reflux Questionnaire (GERDQ) and the Brief Esophageal Dysphagia Questionnaire (BEDQ)]. We used validated Spanish versions of each score 20‐23 …”
Section: Methodsmentioning
confidence: 99%
“…To evaluate convergent validity, several self‐report symptomatic scores were filled by patients, for the evaluation of mood [EHAS and Hospital Anxiety and Depression Scale (HADS) and esophageal symptoms (Eckardt score, Gastroesophageal Reflux Questionnaire (GERDQ) and the Brief Esophageal Dysphagia Questionnaire (BEDQ)]. We used validated Spanish versions of each score 20‐23 …”
Section: Methodsmentioning
confidence: 99%
“…In that study, Taft showed only fair reliability (with Cronbach's α and Guttmann statistic below 0.7) and validity of ES in achalasia patients. Cisternas et al recently reported that ES showed Cronbach's α of 0.57 and 0.65 in non‐achalasia and achalasia, respectively 12 . These studies question the appropriateness of ES use, as it has been suggested that a Cronbach's α > 0.7 is appropriate for clinical use 13…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus is that a PRO should have a Cronbach's alpha ≥0.7 to be used in clinical trials 4,28 . Our groups have recently published psychometric evaluations in large different populations, showing remarkable similar results, with Cronbach's alpha for ES between 0.57 and 0.67 14,15 and between 0.90 and 0.91 for BEDQ 18,19 …”
Section: Discussionmentioning
confidence: 97%
“…Before performing the HRM, all patients filled forms for epidemiological data and responded to several symptomatic scores, including the ES, Gastroesophageal Reflux Questionnaire (GERDQ), and BEDQ. We used validated Spanish language versions for all the questionnaires 15,19,20 . Reason for referral was extracted from the referring physician's order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation